C-reactive Protein-albumin-lymphocyte Index Is a Useful Indicator for Recurrence and Survival Following Curative Resection of Stage I-III Colorectal Cancer - Tomoaki Bekki; Manabu Shimomura; Takuya Yano; Atsuhiro Watanabe; Sho Ishikawa; Kouki Imaoka; Kosuke Ono; Keiso Matsubara; Tetsuya Mochizuki; Minoru Hattori; Shintaro Akabane; Hideki Ohdan (Journal of the Anus, Rectum and Colon)
Objectives: Recently, several simple inflammation-based prognostic scores that can be calculated easily from serum parameters, have been reported to be related to colorectal cancer prognosis. This study aimed to investigate factors influencing the prognosis of patients, including inflammation-based prognostic scores, with stage I-III colorectal cancer following curative resection. Methods: This single-center study included 608 patients with stage I-III colorectal cancer who underwent curative resection between April 2010 and December 2018. A retrospective analysis was performed to identify the prognosis-associated variables in these patients. As a multi-center study, the Hiroshima Surgical study Group of Clinical Oncology database was used to analyze 1659 patients with stage I-III colorectal cancer who underwent curative resection to confirm the results of our single-center study. Results: Of the inflammation-based prognostic scores, only preoperative C-reactive protein-albumin-lymphocyte index was revealed to predict a poor prognosis in patients with stage I-III colorectal cancer following curative resection. The low C-reactive protein-albumin-lymphocyte index was associated with poor overall survival and recurrence-free survival, which was similar in patients from multi-center database. The C-reactive protein-albumin-lymphocyte index was found to be associated with patient age, systemic condition, comorbidities, and tumor factors. The time-dependent area under the curve for the postoperative proghosis of the C-reactive protein-albumin-lymphocyte index was superior to those of other inflammation-based prognostic scores in most postoperative observation periods. Conclusions: The preoperative C-reactive protein-albumin-lymphocyte index was independently associated with long-term prognosis in patients with stage I-III colorectal cancer following curative resection.